Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar Kimia Siswa SMA Negeri 1 Takalar - Asis, Yupriana (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to improve chemistry learning outcomes in SMA Negeri 1 Takalar students through the application of a problem-based learning model. This study uses a classroom action research method. The subjects of this study were 38 students of class X IPA1. Data collection was carried out through observation, tests, and documentation. The data analysis technique of this research is using descriptive analysis. The results of this study indicate that in the first cycle the average score of student learning outcomes was 8.04 in the high category, in the second cycle the average score of learning outcomes was 8.84 with the very high category. Based on the results of this analysis, it can be concluded that the learning outcomes of students in class X IPA1 chemistry can be improved through the application of problem-based learning models.